2018
DOI: 10.15517/rbt.v66i4.31396
|View full text |Cite
|
Sign up to set email alerts
|

Diatom assemblages associated with turtle carapaces in the Neotropical region

Abstract: Few studies have explored the ecology and interrelationship with other organisms of the many endangered freshwater turtle species inhabiting the Neotropical Region. The focus of the current study was to shed light on the relationship between Neotropical turtle carapaces and primary producers, insofar as the surface of former constitutes a suitable substrate for the colonization and establishment of the latter. The under-explored relationship between turtle carapaces and the diatom assemblages inhabiting them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…Epizoic diatoms were present on the carapace of Emys orbicularis, as previously observed on other freshwater (Donato et al, 2018) and marine (Robinson et al, 2016) turtle species. The numbers of species identified were higher than those reported in previous works (Soylu et al, 2006;Robinson et al, 2016;Wu and Bergey, 2017;Donato et al, 2018). This can be explained by differences in sampling protocols or by the higher diversity of diatoms in the sites explored in this study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Epizoic diatoms were present on the carapace of Emys orbicularis, as previously observed on other freshwater (Donato et al, 2018) and marine (Robinson et al, 2016) turtle species. The numbers of species identified were higher than those reported in previous works (Soylu et al, 2006;Robinson et al, 2016;Wu and Bergey, 2017;Donato et al, 2018). This can be explained by differences in sampling protocols or by the higher diversity of diatoms in the sites explored in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Other studies have shown quite different distributions of diatom life forms attached to turtles. In the study of seven freshwater turtle species, a common feature of epibiotic diatoms was the quasi absence of solitary species in favour of colonial forms (Donato et al, 2018), while in the study of seven marine turtle species, adnate forms were dominant (Robinson et al, 2016). Although differences with other substrates were found for the sites Sav and Ver, there is apparently no universal functional community profile characterizing the turtle epizoic habitat.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Estudios realizados con distintas especies de tortugas de agua dulce nativas de la región neotropical indican la presencia de diatomeas como uno de los grupos más diversos y con mayor prevalencia sobre los caparazones de estos reptiles, además sugieren que la rugosidad del caparazón junto al estado de sucesión y la capacidad de adherencia puede explicar esta composición diatomológica. Las características morfológicas de las diatomeas pennadas facilitan la adherencia a distintos sustratos debido al mucilago (lipoproteínas) que generan, además de que se han reportado con una amplia distribución y frecuentes tanto en ambientes eutróficos como oligotróficos (Donato- Rondón et al, 2018;Valdivia, 2019).…”
Section: Discussionunclassified